Analisis Dukungan Keluarga, Ketersediaan Fasilitas Ruang Laktasi dengan Pemberian Asi Eksklusif pada Ibu Bekerja - Desi Ekawati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
ABSTRACTBackground: Breast milk plays an important role in maintaining the health and survival of babies because breast milk is the best food for babies, mothers who have not exclusively breastfed, one of which is working mothers because there are many factors that influence breastfeeding for working mothers. This study aims to analyze the biopsychosocial and institutional factors of exclusive breastfeeding Subjects and Methods: An observational analytic study with a cross sectional design. The research location is in Bantul district. The research time was in March 2018 with 45 research subjects. Sampling used simple random sampling to determine the proportion of research subjects. The dependent variable is exclusive breastfeeding. The independent variables are family support, availability of lactation room. The data obtained using a questionnaire. Analysis using logistic regression analysis. Results: availability of lactation room (OR=4.15; 95% CI= 1.21 to 14.29; p=0.023), family support (OR=4.82; 95% CI= 1.45 to 15.96; p=0.010), has a positive effect on exclusive breastfeeding . Conclusion: Family support, availability of lactation room, has a positive relationship with exclusive breastfeeding. Perception of barriers has a negative relationship with exclusive breastfeeding Keywords: exclusive breastfeeding, health support, working mother